Clinical Presentation, Imaging, and Management of Segmental Arterial Mediolysis: A Rare Vascular Disorder - Alavandar, Ezhilmathi; Umapathy, Shobana; Poyyamoli, Santhosh; Arunachalam, Venkatesh Kasi; Mehta, Pankaj; Cherian, Mathew (Indian Journal of Radiology and Imaging, 2021)
Objectives Our objective was to analyze the clinical presentation, imaging findings, and the management of segmental arterial mediolysis (SAM) in different case scenarios within our medical institution.Materials and Methods We retrospectively analyzed 13 cases of SAM in our institution from July 2017 to March 2020. The images from the cases were collected from picture archiving and communication system (PACS) along with other pertinent clinical information from the hospital's information system. All the patients we studied underwent contrast-enhanced computed tomography (CT) using a third-generation Siemens SOMATOM Force dual-source CT scanner. Once the dual-phase scanning was completed, the images were analyzed using the workstation's syngo.via software.Results Three out of the 13 cases required stent-grafting of the renal/celiac artery, and the involved branch of the superior mesenteric artery was embolized in one case. The rest of the cases were managed conservatively with antiplatelets/anticoagulants. Subsequent follow-ups of the patients were conducted and showed stabilization/regression of the initial findings without finding any evidence of worsening.Conclusion SAM should be considered when making a differential diagnosis of acute abdominal pain when associated with dissection or aneurysms in splanchnic arteries, and in cases of unexplained intra-abdominal hemorrhaging. The radiologist needs to be aware of this possibility to raise suspicion, alert the clinician, and guide appropriate management.
Keywords: dissection; embolization; hemorrhage; management; segmental arterial mediolysis